THE FREQUENCY OF ADRENAL INSUFFICIENCY IN ADOLESCENTS AND YOUNG ADULTS WITH THALASSEMIA MAJOR VERSUS THALASSEMIA INTERMEDIA IN IRAN - Sara Matin; Masoud Ghanei Jahromi; Zohreh Karemizadeh; Sezaneh Haghpanah; Vincenzo De Sanctis; Ashraf Soliman; Mehran Karimi (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Endocrine dysfunction is not uncommon complication in patients with transfusion dependent thalassemia and is thought to occur as a consequence of excessive iron overload. The main objective of this study is to determine the frequency of adrenal insufficiency in patients with thalassemia major and thalassemia intermediate. Methods: This cross-sectional study was done at the Shiraz University of Medical Sciences, Shiraz, Southern Iran, in 2013. One hundred and ninety patients were divided into two groups; thalassemia major(TM) and thalassemia intermediate (TI) groups. We measured 8 AM serum cortisol, ACTH and ferritin concentrations in all patients. Results: The mean age of the TM and TI group were 22.5±5.7 and 23.8±6 years, respectively. 90 patients (47.4%) were splenectomized,  34 (36.2%) with TM and  56 (58.2%) with TI (p : 0.001). The mean serum ferritin levels were 3056.5±2306 and 666.2±616.5 in TM and TI respectively (p: 0.001).  Three patients with TM (1.6%) had low basal cortisol and ACTH levels. However their cortisol response to ACTH stimulation was normal. Conclusions: Low basal concentrations of cortisol and ACTH occurred in 1.6% of our adolescents young adult patients with TM suggesting a central defect of cortisol secretion at the basal state. However, cortisol response to standard – dose ACTH was normal in all patients with TM and TI.